Risk factors for pericardial effusion in adult patients receiving allogeneic haematopoietic stem cell transplantation. (27th March 2015) - Liu, Yao‐Chung; Chien, Sheng‐Hsuan; Fan, Nai‐Wen; Hu, Ming‐Hung; Gau, Jyh‐Pyng; Liu, Chia‐Jen; Yu, Yuan‐Bin; Liu, Chun‐Yu; Hsiao, Liang‐Tsai; Liu, Jin‐Hwang; Chiou, Tzeon‐Jye; Tzeng, Cheng‐Hwai
Summary Pericardial effusion (PE) is a rare but potentially life‐threatening complication for allogeneic haematopoietic stem cell transplantation (HSCT) recipients. The risk factors, aetiology, incidence and therapy are largely unclear. To investigate this issue, we reviewed 391 adult patients undergoing allogeneic HSCT between January 2003 and December 2013. Twelve out of 391 patients (3·1%) developed PE of moderate to large amounts, including 9 out of 12 patients (75%) identified as late‐onset PE. Two out of the nine patients with late‐onset PE experienced recurrent effusion. The median age at HSCT was 44·5 years (range: 22–63 years) among the 12 patients with PE and 47 years in the late‐onset patients. Multivariate analysis revealed that multiple transplant procedures was a significant risk factor for PE (P = 0·036) and a trend as risk factor in patients aged>50 years (P = 0·066). For late‐onset PE, pre‐transplant age>50 years (P = 0·032) and extensive chronic graft‐versus‐host disease (cGVHD) (P = 0·006) remained statistically significant on multivariate analysis. Currently, there are no published data exploring the risk factors for post‐transplant PE in adult patients of allogeneic HSCT. Our study determined the risk factors and incidence for the post‐transplant PE, especially in the late‐onset group.